An Assessment Of Problems Faced By Female Students Residing In Hostel At University Of Agriculture Faisalabad - Rizwan Ahmad; Mehwish Shoukat; Umm E Habiba; Khadeeja Saeed (International Journal of Economics, Business and Innovation Research, 2023)
Hostel is a type of accommodation that provides shared living spaces for travelers and students. Hostels usually offer dormitory-style rooms with multiple bedrooms as well as shared bathrooms. Students living in hostel share their space with each other. A hostel for student is a type of accommodation provided by educational institutions. In addition to offering accommodations, a hostel caters to the fundamental necessities of students. The purpose of this study was to evaluate the challenges encountered by female students who live in the University of Agriculture Faisalabad’s hostel and the effect of these problems on academic performance of female students residing in hostels. The study further identified several common problems faced by female students, including inadequate infrastructure and facilities, limited social support, difficulties in managing academic workload, and issues related to privacy and personal space. There are 10 female hostels in University of Agriculture Faisalabad, out of which 5 female hostels were selected randomly. From each hostel 25 students were selected through random sampling technique. A well-developed questionnaire was used to collect data. Collected data was analyzed by using Statistical Packages for Social Sciences (SPSS). Results of the study showed that more than half (58%) of the respondents were between 25 to 30 years old. Large majority (70%) of the respondents were in master. Large majority (85%) of the respondents belonged to urban areas. Lack of privacywith mean value 4.33, lack of variety in meal optionswith mean value 4.30, high cost of accommodationwith mean value 4.29 were the common problems faced by female students in the hostel. Irregular sleep patterns was at rank ordered on 1st positionand it showed that the responses fell between the agree to strongly agree and tending towards the agree with mean value 4.38, mental exhaustionwith mean value 4.40 were major impact of hostel life on physical health of female students. Restriction and limited freedom with mean value 4.53, stereotypingwith mean value 4.40 were main social problems faced by female students residing in the hostel. It was concluded that numerous troubles and obstacles including lack of privacy, medical facilities, money related emergencies, alteration issues, individual weakness, distress, changes in eating and rest propensities, and many other issueswere encountered by female students in their hostel life. Effective solutions should be addressed to improve the living conditions of female students living in university hostels.